Adoptive transfer of allergen-expressing B cells prevents IgE-mediated allergy - Prickler, Lisa; Baranyi, Ulrike; Mengrelis, Konstantinos; Weijler, Anna Marianne; Kainz, Verena; Kratzer, Bernhard; Steiner, Romy; Mucha, Jasmin; Rudoph, Elisa; Pilat, Nina; Bohle, Barbara; Strobl, Herbert; et al. (Frontiers in Immunology, 2023)
Prophylactic strategies to prevent allergy development through establishing tolerance remain an unmet medical need. We previously reported that the transfer of autologous hematopoietic stem cells (HSC), expressing the major timothy grass pollen allergen, Phl p 5, on their cell surface, induced allergen-specific tolerance in mice. In this study, we investigated the ability of allergen-expressing immune cells (dendritic cells, CD4 + T cells, CD8 + T cells, CD19 + B cells) to induce allergen-specific tolerance in naïve mice and identified CD19 + B cells as promising candidates for allergen-specific cell therapy. For this purpose, CD19 + B cells from Phl p 5-transgenic BALB/c mice were isolated and transferred to naive BALB/c mice, pretreated with a short course of rapamycin and anti-CD40L antibody. Subsequently, mice were sensitized subcutaneously three times in 4-week intervals to Phl p 5 and Bet v 1 as unrelated control allergen. Allergen-expressing cells were followed in the blood to monitor molecular chimerism and sera were analyzed for Phl p 5-and Bet v 1-specific IgE and IgG1 levels by RBL assay and ELISA, respectively. In-vivo allergen-induced lung inflammation was measured by whole body plethysmography and mast cell degranulation was determined by skin testing. The transfer of purified Phl p 5-expressing CD19 + B cells to naive BALB/c mice induced B cell chimerism for up to three months and prevented the development of a Phl p 5-specific IgE and IgG1 antibody responses for a follow-up period of 26 weeks. Since Bet v 1-but not Phl p 5-specific antibodies were detected, tolerance induction was specific for Phl p 5. Whole body plethysmography revealed preserved lung function in CD19 + B cell-treated mice in contrast to sensitized mice and there was no Phl p 5-induced mast cell degranulation in treated mice. Thus, we demonstrated that transfer of Phl p 5-expressing CD19 + B cells induces allergen-specific tolerance in a mouse model of grass pollen allergy. This approach could be further translated into a prophylactic regimen for the prevention of IgE-mediated allergy in humans.